The global employment challenge - Ghose, Ajit Kumar, 1947-; Majid, Nomaan; Ernst, Christoph (International Labour Office, 2008)
This volume offers an in-depth analysis of the state of employment in the world today, providing a detailed and comprehensive picture of the serious challenges faced by today's policy-makers ...